Current State and Trends of Access to Sanitation in Ethiopia and the Need to Revise Indicators to Monitor Progress in the Post-2015 Era - Beyene, Abebe (BioMed Central, 2015)
Investigating the current level and trends of access and identifying the underlying challenges to sanitation system development will be useful in determining directions developing countries are heading as they plan to promote sustainable development goals (post 2015 agenda). This research investigates the status and trends of access to improved sanitation coverage (ISC) in relation to the MDG target in Ethiopia with the aim of identifying prevailing constraints and suggesting the way forward in the post-MDG era.